Illocutionary Speech Acts and Kinesics: An Analysis of President BBM’s Selected Speeches - Hans Bonotan; Lyka Dela Cerna; Ave Marie Dongallo; Mary Joy Galon; Joemar Minoza (Universitas Pendidikan Mandalika, 2026)
This study analyzes the illocutionary acts and nonverbal cues in President BBM's speeches, employing Illocutionary Speech Act Theory to categorize speech acts and Kinesics Theory to examine nonverbal communication. Three speeches are analyzed: Miting de Avance, the Inaugural Speech, and the State of the Nation Address (SONA). Expressive acts are most common in Miting de Avance, while representative acts dominate the Inaugural Speech and SONA. President BBM uses expressive acts to demonstrate affection for Filipinos and representative acts to assert facts or beliefs. Nonverbal analysis reveals that facial expressions are prominent in Miting de Avance, conveying a wide range of emotions, whereas head movements are more common in the Inaugural Speech and SONA, facilitating communication and social interaction. These findings highlight how the interplay between illocutionary acts and nonverbal cues shapes political communication, offering insights into how leaders strategically engage audiences and influence public speaking practices. However, the study is limited to three speeches, which may not fully capture the breadth of the president’s communicative repertoire. Future research could expand to comparative analyses across multiple political figures or contexts to deepen understanding of how speech acts and kinesics jointly affect audience perception and political discourse.